DAMPAK STEPPER AEROBIK TERHADAP KESEHATAN KARDIOVASKULAR IBU-IBU USIA 30–50 TAHUN - Hartini; Kodrad Budiyono; Muhammad Adib Farhan; Muhammad Ilham Albadawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cardiovascular disease remains one of the leading causes of mortality worldwide, with the risk increasing among women aged 30–50 years due to physiological changes, sedentary lifestyles, and insufficient physical activity. Step aerobic exercise is a practical and accessible form of aerobic training that may improve cardiovascular health. This study aimed to examine the effect of step aerobic exercise on cardiovascular health among women aged 30–50 years. A quasi-experimental pre-test and post-test control group design was employed. The study involved 40 participants, who were equally assigned to an experimental group (n=20) and a control group (n=20). The experimental group participated in a 12-week step aerobic exercise program, three sessions per week, with each session lasting 30–45 minutes, while the control group received no exercise intervention. Cardiovascular parameters assessed included systolic and diastolic blood pressure, resting heart rate, maximal oxygen uptake (VO₂max), and body mass index (BMI). Data were analyzed using descriptive statistics, paired t-tests, and independent t-tests at a 5% significance level. The results indicated that the experimental group experienced significant reductions in systolic blood pressure (10.5 mmHg), diastolic blood pressure (6.2 mmHg), resting heart rate (8.8 beats/min), and BMI (0.7 kg/m²), along with an 18.2% increase in VO₂max (p<0.05). No significant changes were observed in the control group. In conclusion, step aerobic exercise effectively improves cardiovascular health by enhancing blood pressure, cardiac efficiency, aerobic capacity, and body composition in women aged 30–50 years. This exercise program may serve as an effective promotive and preventive strategy for reducing cardiovascular disease risk.